Mid-gestational exposure to histone deacetylase inhibitor suberoylanilide hydroxamic acid influence cortical interneuron and astrocyte in mouse brain - Nunung Yuniarti; Berry Juliandi; Tsukasa Sanosaka; Kinichi Nakashima (Indonesian Journal of Biotechnology, 2017)
Suberoylanilide hydroxamic acid (SAHA) has been reported preclinically to diffuse across the placenta and to be found in fetal plasma, suggesting that it can influence the fetus if taken by a pregnant cancer patient. In utero exposure of SAHA to mouse embryos during mid-gestation was found to perturb corticogenesis. However, the influence of in utero administration of SAHA to mouse embryos during mid-gestation on astrocyte, glial cell, and inhibitory neurons (interneurons) is yet to be reported. Pregnant dams were divided into control and SAHA groups and given methyl cellulose (as control) and SAHA orally once a day for 3 days during mid-gestation, starting from embryonic day (E)12 until E14. Astrocyte, interneuron, and behavior analyses were performed on the pups from postnatal day 7 until adulthood (3 months old). Brains were harvested and immunohistochemistry, Western Blot, and RT-PCR were performed on their cortex area. Transient exposure of SAHA to mouse embryos resulted in a decrease and increase in cortical astrocyte and interneuron, respectively. Meanwhile, adult SAHA mice displayed significantly increased anxiety, decreased memory, altered long-term cognitive functions, and reduced social interactions. Our study suggests that exposure to SAHA during prominent neurogenic periods might imbalance the normal excitatory:inhibitory neuron ratio required for the precise regulation of physiological functions in the brain.